Developing and Using Fill-in-the-Blank Tasks for Online Courses on the Stepik Platform - Bagoutdinova, Alfiya (Computer Tools in Education, 2025)
The article examines the experience of creating and using "Fill-in-the-blanks"tasks in the online courses "Linear Algebra and Analytical Geometry"and "Probability Theory and Mathematical Statistics."These courses were specifically developed as a supplement to in-person classes for students of the Institute of Management, Economics, and Finance at Kazan Federal University and are hosted on the Stepik educational platform. A significant portion of the practical tasks in these courses is presented in the "Fill-in-the-blanks"format, which is highly effective. The key feature is that a single test item can incorporate several questions interspersed with text. This format allows not only for assessing the student’s f inal answer but also for tracking their entire reasoning process when solving a problem. The paper provides specific examples from the courses that illustrate the capabilities of fill-in-the-blanks tasks and offers recommendations for their effective use. Empirical data confirm the positive impact of the courses’ implementation, including a 9.5% increase in the average score and a reduction in the proportion of unsatisfactory grades on topics that were previously challenging.This article will be useful for educators interested in developing effective assignments to enhance the quality of education and student motivation in online or hybrid learning environments.
Keywords: “Fill-in-the-blanks” tasks; Stepik educational platform; online mathematics courses